Pengaruh Mekanisme Good Corporate Governance terhadap Kinerja Keuangan Perusahaan Sektor Infrastruktur Tahun 2020-2024 - Arsipah Arsipah; Taufik Azis; Surono Surono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of Good Corporate Governance mechanisms on financial performance in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The GCG mechanism in question includes institutional ownership, board of directors, board of commissioners, and audit committee. The company's financial performance is measured using the Return on Assets (ROA) indicator. This research approach uses quantitative methods with panel data regression analysis techniques. The population in this study consisted of all infrastructure companies listed on the IDX during the observation period, and purposive sampling technique was used to determine the sample in accordance with certain criteria. The test results show that partially, only the audit committee variable has a positive and significant effect on financial performance. Meanwhile, the variables of institutional ownership, board of directors, and board of commissioners did not show a significant effect. These findings reinforce the importance of the audit committee's role in overseeing and ensuring effective governance to support the improvement of the company's financial performance.